The Lexical and Phonetical Features of The Tengger Dialect of Javanese - Sri - Andayani (Metathesis: Journal of English Language, Literature, and Teaching, 2018)
Probolinggo, East Java is an area of Pandalungan. Culturally, the area has the mixing of Javanese and Madurese cultures, so as the local languages that are used by the society. Most of Probolinggo people master Javanese as well as Madurese language. Besides, there is one more dialect developing in Probolinggo, that is Tengger dialectdialect. It is used by the Tengger society in Tengger Mountainuos region around Mount Bromo. The Javanese that is used by the Tengger society is different from the Javanese of Probolinggo or even the standard Javanese. The significant difference is in the pronunciation of the vowel. It tends to have the features of the Old Javanese. By doing Comparative Historical Linguistics study, the features of Tengger dialect compared to the Modern and Old Javanese. The qualitative descriptive study uses an observation method to collect the data. Then, they are analyzed by the distributional and identity methods. It indicates that the distribution and development of Javanese as a part of Austronesian language family is not merely innovatively. It can be relix likewise. The Tengger dialect phonetical and lexical features tends to be similar to the Old Javanese feature, not the modern ones as the innovative Javanese.